(untitled) (GEON Journal (Management, Organizations and Business), 2014)
The management of human resources becomes a fundamental activity within the administrative process that runs on each organization, being key to the development and implementation of strategies that will enable the organization to survive and compete in an environment. In the last decades have shown a clear shift in the conception of the importance and relevance of human talent for organizations, in such a way that many companies have changed their philosophy and vision about how to manage people so that they align with the mission, objectives and goals of each, resulting in a host of tools and modern theories that focus on how to manage and motivate human talent within companies. The Employer Branding is a tool for the management of human talent which allows a strong alignment between employees and the organization, taking as a fundamental element of the strategy of the brand positioning in the labor market, for such achievement is used as a vehicle internal customers or collaborators